2013
DOI: 10.1097/cpm.0b013e31828fc487
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation as Adjunctive Therapy for Refractory Hypoxemic Respiratory Failure in HIV-positive Patients With Severe Pneumocystis jirovecii Pneumonia

Abstract: In the United States, Pneumocystis jirovecii (PCP) is a leading cause of morbidity and mortality in hospitalized patients with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) and can result in severe hypoxemia despite maximal conventional ventilator support. We present 2 adult patients with HIV/ AIDS and PCP who were managed with extracorporeal membrane oxygenation (ECMO) because of refractory hypoxemia. After prolonged hospitalization, the first patient developed multiorgan failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Several case reports and small series describe the use of ECMO in patients with HIV and respiratory failure. [3][4][5][6][7][8][9][10][11][12][13][14][15] The bias toward reporting successful cases is evident in the 93% survival of the 14 patients reported in these studies. In another study, Capatos et al 16 describe an aggressive approach to the management and cannulation of HIV patients with severe respiratory failure within three institutions in South Africa, with the authors reporting a survival to discharge among their 22 patients of 68% in all patients and 60% in those with Pneumocystis jirovecii pneumonia (PJP).…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports and small series describe the use of ECMO in patients with HIV and respiratory failure. [3][4][5][6][7][8][9][10][11][12][13][14][15] The bias toward reporting successful cases is evident in the 93% survival of the 14 patients reported in these studies. In another study, Capatos et al 16 describe an aggressive approach to the management and cannulation of HIV patients with severe respiratory failure within three institutions in South Africa, with the authors reporting a survival to discharge among their 22 patients of 68% in all patients and 60% in those with Pneumocystis jirovecii pneumonia (PJP).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of timing of ECMO initiation, it seems ideal to start ECMO within 7 days from ventilator introduction based on the ELSO guideline 12 and Respiratory ECMO Survival Prediction (RESP) score. 14 In addition, as Goodman et al 4 reported, patients given ECMO early during their ventilator management course showed higher survival rates (Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…There are several reports of successful ECMO use for severe hypoxia in patients with HIV/AIDS. [2][3][4][5][6][7][8][9][10] However, key therapeutic issues, such as mechanical ventilation (MV) settings, indications for ECMO, and the timing of antiretroviral therapy (ART), have not always been discussed in these reports. A case of acute respiratory distress syndrome in a patient with novel HIV/ AIDS, who was successfully treated with veno-venous (V-V) ECMO and discharged, is presented.…”
mentioning
confidence: 99%
“…As for the timing of ECLS initiation in PJP, Goodman [10] reported that apart from higher survival rates, the early usage of ECMO during the course of MV can result in a shorter duration of ECMO support in patients. Similarly, Obata [20] also reported that early ECMO introduction can produce early achievement of lung rest management.…”
Section: Discussionmentioning
confidence: 99%